Peran Perencanaan Keuangan dalam Mendukung Efektivitas Operasional Sekolah - Restu Agung Santoso; Ummi Mardiyah (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Good financial planning can create operational effectiveness in educational institutions. This article analyzes the importance of financial planning in school management, covering aspects such as the development of facilities and infrastructure, the improvement of student learning quality, and teacher welfare. The research method used is quantitative with a library research approach, where data is obtained from various scholarly articles and relevant books sourced from Google Scholar. The findings indicate that schools effectively apply for funding and evaluate fund utilization annually. Poor financial planning can disrupt school operations, leading to issues such as delayed teacher salaries, insufficient learning facilities, and other challenges. To achieve effective financial management, technological mastery is essential to ensure operations that are effective, efficient, and accountable.